Purpura Fulminans Induced by Disseminated Intravascular Coagulation following Infection in 2 Unrelated Children with Double Heterozygosity for Factor V Leiden and Protein S Deficiency - Inbal, Aida; Kenet, Gilly; Zivelin, Ariella; Yermiyahu, Tikva; Bronstein, Tamar; Sheinfeld, Tomy; Tamari, Hana; Gitel, Sanford; Eshel, Gill; Duchemin, Jerome; Aiach, Martine; Seligsohn, Uri (Thrombosis and Haemostasis, 1997)
Purpura fulminans is associated with homozygous protein C and homozygous protein S deficiency or may follow bacterial or viral infections. We present 2 children from 2 unrelated Arab families with purpura fulminans who were double heterozygotes for factor V Leiden inherited from their fathers and protein S deficiency inherited from their mothers. No previous thrombotic events have occured in either patient or their respective family members. In one patient sepsis accompanied by disseminated intravascular coagulation appeared to be the trigger of purpura fulminans. In the other patient varicella infection preceded purpura fulminans and was also associated with disseminated intravascular coagulation. This report emphasizes the need for evaluation of hereditary defects in the inhibitory mechanisms of blood coagulation in patients with purpura fulminans at any age.